Liver transplantation for homozygous familial hypercholesterolaemia. Issue 5 (November 1995) - Revell, S P; Noble-Jamieson, G; Johnston, P; Rasmussen, A; Jamieson, N; Barnes, N D
Abstract : Homozygous familial hypercholesterolaemia is a rare inherited condition with an incidence of approximately one in a million. It is associated with severe premature atherosclerosis and early death from cardiovascular complications. The results of liver transplantation reported to date have suggested only partially effective reduction of the hypercholesterolaemia. Three boys with familial hypercholesterolaemia, aged 10.0 to 15.1 years, received liver grafts at Addenbrooke's Hospital. Their untreated fasting lipid concentrations were grossly raised. All three had angiographic evidence of coronary atheroma and two had exertional angina. One child had such severe atheroma that coronary artery bypass surgery was considered necessary before liver transplantation. All three had straightforward operative and postoperative courses and their lipid concentrations returned rapidly to normal. One boy developed chronic rejection requiring retransplantation. Currently all three boys are well, on normal diets, and with normal liver function. It is concluded that (1) liver transplantation offers highly effective treatment for this lethal condition, (2) timing the operation is difficult but it should be undertaken before coronary artery disease has progressed too far (when combined liver and heart transplantation may be the only possibility), and (3) in well grown children with no previous abdominal surgery the immediate risks of liver transplantation are low but chronic rejection remains a danger.